Unani preparation ‘Sharbat Misali’ is useful as an alternate medicine to safely treat anemia: A pilot study - Nargis, Nazlima; Mahmood, Abu Kholdun Al; Afrin, Syeda Fahmida; Sayeed, M Hasan; Hassan, Md Zahid (Bangladesh Journal of Medical Science, 2018)
Background: Unani Medicine had its golden past in the middle age. Allopathic medicine evolved with simultaneous exploration of modern scientific development. Discovery of chemicals and antibiotics to deal infectious disease led foundation of epitome of modern medicine. There is however growing tendency among people to show their to depend on plant source and time old preparations. It is estimated that about 80 percent of population of the Asia and African countries uses herbal medicine for health care. This scenario opened the scope and merit to evaluate the preparation(s) which people are still using and the present study tested the usefulness and safety of ‘Sarbat Misali’ an Unani hematinic preparation in treating anemia. Materials and Methods: A total 31 women of age 24-40 yrs were enrolled in the study following ethical guidelines. The volunteers offered the choice and were free to refuse for not being included. Anthropometry recorded and blood sample obtained for biochemical test from the consenting subjects and prescribed with the preparation. Weight recorded and blood samples taken at the baseline end of four weeks. During study period they were in touch for their allegiance to taking the test preparation. Hemoglobin was estimated using autoanalyzer. Serum creatinine and SGPT were determined by standard biochemical method using autoanalyzer. Results: Blood hemoglobin level showed significant increase at the end of the supplementation (12.03±0.82) compared to the baseline level (10.78±1.08) (p<0.001). Serum creatinine and SGOT did not show any statistical difference between before and after supplementation. Conclusion: Data concluded that Sharbat Misali an Unani preparation of hematinics improved hemoglobin level and safety was supported by the fact of unaltered hepatic and renal functional status, however, to conclusively comment on adverse and toxic effect(s) chronic study needs to be undertaken with attention of inclusion of exhaustive biochemical markers. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.144-148